Pengaruh Kualitas Pelayanan, Harga Dan Experience Marketing Terhadap Minat Beli Ulang Pada Kedai Goli Bima - Denti Eka Wahyuningsih; Yusi Faizathun Octavia; Satriawan (Kredibel: Jurnal Ilmiah Manajemen, 2026)
This research aims to determine the influence of service quality, price and marketing experience at Kedai Goli Bima. The population in this research is all customers the number of which is not known for certain. Samples were taken using purposive sampling. The data collection technique used was a questionnaire involving 40 respondents who made purchases within the last 2 months. The data analysis technique used is a multiple linear regression analysis technique with the results Y = 171.952 + -0.146X1 + 0.187X2 + 0.475X3 calculated using the SPSS 27 program. Based on the results of the multiple linear regression test it can be concluded that the constant value is 171.952, which means if not there is a change in the variables of service quality, price and Marketing Experience (the values of X1, X2, and X3 are 0). So, repurchase interest at Kedai Goli Bima is 171,952 units. The results of this research also show that the t-test (partial) states that the service quality variable is not significant, the price variable has a positive is not significant, the experience marketing variable has a positive and significant effect. Based on the F test (simultaneous), it states that the variables of service quality, price and Marketing Experience have a simultaneous influence on repurchase interest and the beta test shows that the variables have a dominant influence on repurchase interest in shops. Goli Bima is an experience marketing variable.